Genetic improvement study on pre-weaning body weight of Egyptian Rahmani lambs under a pure breeding production system - El Awady H.G.; Oudah E.Z.M.; Shalaby N.A.; El Arian M.N.; Metawi H.R. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Body weight records of 2824 purebred Egyptian Rahmani lambs born from 946 ewes sired by 109 rams were collected from 1991 till 2001 to estimate genetic parameters and to predict breeding values (BV) for birth weight (BW), 60-day (W60) and 120-day body weight (W120) using two statistical models. The 1st model included direct additive genetic variance and residual. The 2nd model included (beside model 1) maternal genetic variance, direct-maternal genetic covariance and permanent environmental variance. Genetic parameters and breeding values were estimated by a multiple-trait animal model using derivativefree restricted maximum likelihood method (MTDFREML). Direct heritability estimates for BW, W60 and W120 were 0.40, 0.42 and 0.40, respectively using the 1st model and 0.64, 0.26 and 0.29 using the 2nd model. For BW, W60 and W120, maternal heritability estimates were 0.47, 0.17, and 0.10, total heritability estimates were 0.50, 0.53 and 0.34. Direct-maternal genetic correlations were -0.40, 0.59 and 0.01. Repeatability estimates were 0.57, 0.79 and 0.58, respectively. Phenotypic variance due to maternal permanent environmental effects (c2) increased with decreasing maternal heritability with old ages. The Spearman correlation between estimated breeding values of studied body weights by both models was high (0.52 to 0.99). These results indicate a strong maternal influence in this herd and the presence of sufficient genetic variation to allow mass selection for growth traits.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)